(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
Effect of insertion combined screw and twisted tapes in a heated tube fitted with converge-diverge conical turbulators on Nusselt number, friction factor and overall performance factor has been experimentally investigated. The air is the working fluid for Reynolds number variety of 15000-65000. The conical nozzles used as turbulators are located inside the heated tube with the combined twisted and screw tapes. The considered compound case is compared with the single twisted and screw tape. The twisted tape is used for three various twist ratios (Y/W=3.0,5.0,and 7.0), while the screw tape for one screw ratio equal to 3.0 . It is discovered that the combined tapes with conical turbulators enhance considerably the heat transfer over that of the conical turbulators alone by about 47.7% and 43.18%,and 39.7% for twist ratio of 3.0,5.0 and 7.0 respectively. The optimal thermal performance is pointed for screw and twist ratio equal to 3.0 .